EFEKTIVITAS TERAPI RELAKSASI OTOT PROGRESIF TERHADAP GANGGUAN PERFUSI PERIFER PADA PASIEN DIABETES MELLITUS TIPE 2: STUDI KASUS DESKRIPTIF KUALITATIF - Erva Elli Kristanti; Imanuela Omega Saswitawati (Suluh Adiluhung Publisher (SAPub), 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia due to insulin resistance and beta-cell dysfunction. Chronic hyperglycemia leads to microvascular complications, including ineffective peripheral tissue perfusion. Progressive Muscle Relaxation (PMR) may enhance peripheral circulation through vasodilation mechanisms. The objective was to describe nursing care implementation in T2DM patients with ineffective peripheral perfusion using PMR therapy. A qualitative descriptive case study involving two hospitalized T2DM patients. Data was collected through in-depth interviews, systematic observation, focused physical examination, and medical records review. PMR was administered for 3–5 minutes per session for two days. The results showed prior to intervention, patients presented paresthesia (5–6/10), cold extremities (34.1–34.5°C), pale skin, and capillary refill time >3 seconds. After intervention, paresthesia decreased (2–3/10), extremities became warmer (36.0–36.3°C), capillary refill time improved (<2 seconds), and skin color normalized. In conclusion that PMR demonstrates potential as a non-pharmacological nursing intervention to improve peripheral perfusion in T2DM patients.